Perancangan Card Game Lingkaran Kebiasaan dengan Ilustrasi Komik Strip pada Kehidupan Sehari-hari Remaja - Mohammad Candra Al-Aliyyu; Restu Ismoyo Aji; Mahimma Romadhona (VISA: Journal of Vision and Ideas, 2026)
Habits are behaviors formed through repetition and are often performed automatically in everyday life. In late adolescence (18–21 years), the process of habit formation is strongly influenced by the social environment, but based on the results of FGDs and questionnaires, adolescents are not yet fully aware of the habit patterns they are experiencing and how to change them. This design aims to design a card game entitled "KeBiasaCard" which raises the concept of the habit loop through cartoon-style comic strip illustrations as an interactive and fun media for adolescents. The method used is the Seven Stages of Design (Ambrose & Harris, 2010) which includes the stages of define, research, ideate, prototype, select, implement, and learn, with data collection in the form of literature studies, interviews, observations, and FGDs. The design results in a card game consisting of 26 habit cards representing the four stages of the habit loop: cue, motivation (craving), response, and reward, as well as 24 interactive cards, with a visual concept using cartoon-style slice-of-life comic strip illustrations and decorative typography. KeBiasaCard is expected to be a medium that can help teenagers recognize and understand the process of habit formation in an interactive and fun way.